1996
DOI: 10.1111/j.1469-8137.1996.tb01844.x
|View full text |Cite
|
Sign up to set email alerts
|

Tissue localization of u.v.‐B‐screening pigments and of chalcone synthase mRNA in needles of Scots pine seedlings

Abstract: (Dedicated to Professor Klaus Hahlbrock on the occasion of his 60th birthday) SUMM.^RY Epidermal tissue was isolated from Scots pine {Pinus sylvestris L.) needles by enzymatic digestion in order to study tissue distribution of u.v,-B-screening pigments. Up to 90 "o ofthe needle content of a group of diacylated flavonoi glycosides tbat were structurally closely related was found in the epidermal layer. Among these metabolites. 3",6"-di-para-coumaroyl-isoquerfitrin and 3",6"-di-para-coum3roy]-astragal in were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
174
1
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(187 citation statements)
references
References 39 publications
9
174
1
3
Order By: Relevance
“…Biosynthesis of flavonoids is often induced under the influence of UV-B radiation in the plants ( Li et al 1993;Jordan 1996;Caldwell et al 1999 andJenkins et al 2009), which may be due to the increased influx of precursor amino acids into their metabolic pathways. This can be seen as a strategy of the plants to overcome UV-B stress through effective absorption shown by the flavonoids in the UV-B spectral region (Reuber et al1996;Schnitzler et al 1996 andHoque andRemus 1999) and by overcoming the oxidative stress in cells (Dawar et al 1998). Despite these favourable effects in the plants, the increased level of flavonoids has been shown to interfere with vital physiological processes such as ATP synthesis and oxidative phosphorylation leading to disintegration of chloroplasts, causing chlorosis and necrosis (Kumari et al 2009).…”
Section: Effects Of Uv-b Exposure On Anthocyanin and Total Flavonoid mentioning
confidence: 99%
“…Biosynthesis of flavonoids is often induced under the influence of UV-B radiation in the plants ( Li et al 1993;Jordan 1996;Caldwell et al 1999 andJenkins et al 2009), which may be due to the increased influx of precursor amino acids into their metabolic pathways. This can be seen as a strategy of the plants to overcome UV-B stress through effective absorption shown by the flavonoids in the UV-B spectral region (Reuber et al1996;Schnitzler et al 1996 andHoque andRemus 1999) and by overcoming the oxidative stress in cells (Dawar et al 1998). Despite these favourable effects in the plants, the increased level of flavonoids has been shown to interfere with vital physiological processes such as ATP synthesis and oxidative phosphorylation leading to disintegration of chloroplasts, causing chlorosis and necrosis (Kumari et al 2009).…”
Section: Effects Of Uv-b Exposure On Anthocyanin and Total Flavonoid mentioning
confidence: 99%
“…For flavonol localization, cover slides were directly placed on slide-mounted tissue sections after the removal of paraffin with toluene. Flavonol autofluorescence (Schnitzler et al, 1996) was observed under green fluorescence (excitation filter, band pass 420-490; dichromatic mirror, 510; suppression filter, long pass 515) using a Leica DMRXA microscope in the fluorescence configuration, and micrographs were taken with a microscope-mounted Nikon camera controlled by ACT-1 software (Nikon). Tissue sections were also stained with the flavonol-specific stain DPBA, using the method of Peer et al (2001).…”
Section: Histological Procedures and Pa And Flavonol Tissue Localizationmentioning
confidence: 99%
“…Trichome frequency was estimated by counting the number of glandular trichomes per unit leaf area at a magnification of i50 (Gravano et al, 1998). Histochemical localization of flavonoids was performed by modifying the protocol proposed by Schnitzler et al (1996). Transverse sections (30 µm) of fresh leaf tissue were stained for 1n5 min in 1% diphenylboric acid 2-amino-ethyl ester (Sigma) in ethanol (Naturstoff reagent).…”
Section: Leaf Morphological-structural Analysis and Histochemical Locmentioning
confidence: 99%